2015
DOI: 10.3389/fnagi.2015.00071
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle mediated drug delivery of rolipram to tyrosine kinase B positive cells in the inner ear with targeting peptides and agonistic antibodies

Abstract: Aim: Systemic pharmacotherapies have limitation due to blood-labyrinth barrier, so local delivery via the round window membrane opens a path for effective treatment. Multifunctional nanoparticle (NP)-mediated cell specific drug delivery may enhance efficacy and reduce side effects. Different NPs with ligands to target TrkB receptor were tested. Distribution, uptake mechanisms, trafficking, and bioefficacy of drug release of rolipram loaded NPs were evaluated.Methods: We tested lipid based nanocapsules (LNCs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 90 publications
(123 reference statements)
0
19
0
Order By: Relevance
“…The Trk family of receptors includes the neurotrophin receptor tyrosine kinase-2 ( NTRK2 ) (TrkB) specific for brain-derived neurotrophic factor (BDNF) and neurotrophin-4 (NT-4) [5]. Both BDNF and TrkB are key factors in the development and maintenance of hearing function [6,7,8,9,10]. Brain-derived neurotrophic factor and its receptor moieties are instrumental to facilitate sensory neuronal survival in embryonic rat [11].…”
Section: Introductionmentioning
confidence: 99%
“…The Trk family of receptors includes the neurotrophin receptor tyrosine kinase-2 ( NTRK2 ) (TrkB) specific for brain-derived neurotrophic factor (BDNF) and neurotrophin-4 (NT-4) [5]. Both BDNF and TrkB are key factors in the development and maintenance of hearing function [6,7,8,9,10]. Brain-derived neurotrophic factor and its receptor moieties are instrumental to facilitate sensory neuronal survival in embryonic rat [11].…”
Section: Introductionmentioning
confidence: 99%
“…We have described the fundamental procedures for dissecting, plating, and culturing early post-natal murine inner ear explants using Millicell culture inserts and serum- free conditions. The use of serum free media for cochlear and vestibular explant culture is becoming more common (Kopke et al, 1997; Cunningham et al, 2002; Amarjargal et al, 2009; Bas et al, 2014; Glueckert et al, 2015; Wu et al, 2018). And, published methods similar to this protocol further validate the efficacy of organotypic cell culture inserts when culturing cochlear or vestibular tissues (Praetorius et al, 2010; Baker and Staecker, 2012; Dammeyer et al, 2014; Defourny et al, 2015; Ma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As with the trisialoganglioside clostridial toxin receptor, phage display has been used to develop binding peptides for these receptors. Recent work has demonstrated that nanoparticles targeted with the TrkB binding A371 peptide bind preferentially to the spiral ganglion's neuronal cells [35], and that this targeting peptide has enabled Rolipram, a phosphodiesterase inhibitor, to be delivered to the mouse spiral ganglia as a potential agent that improves cell survival [35,45]. Additional work has suggested the possibility of targeted delivery of the TrkB agonist, 7,8-dihydroxyflavone (DHF) as a means for increasing neurite growth in the setting of kainicacid cochlear damage [46].…”
Section: Bdnf/nt-3 Growth Factors Receptor (Trkb)mentioning
confidence: 99%